IMPLEMENTASI DYNAMIK ROUTING PROTOKOL OSPF PADA ROUTER DI JARINGAN YATIM MANDIRI - Ayu Merlina Lidya; Astriana Mulyani (Sekolah Tinggi Teknologi Informasi NIIT, 2021)
The National Amil Zakat (LAZNAS) orphans, which is moving to establish the orphans and the Du'afa throughout Indonesia. Dynamik Routing Protcol OSPF is an automatic routing protocol that works to manage, maintain and distribute Routing information between networks to dynamically follow network changes. OSPF is commonly known AS the term Autonomus System (USA) combined from multiple routing networks, has similarity of methods and regulates the network. All of it can be controlled network administrators. Most features are used for management in large large network scales and routing protocols that use a routing hierarchy that can divide a network into multiple tiers. The level used by the grouping system